Material Review of Law Number 20 of 2025 Concerning the KUHAP by an Advocate in the Constitutional Court: A Constitutional Perspective - Fitri Karisma; Effendy Lod Simanjutak (Ridwan Institute, 2026)
The enactment of Law Number 20 of 2025 concerning the Criminal Procedure Code (KUHAP) represents a major reform of Indonesia’s criminal procedural law, aiming to enhance effectiveness, efficiency, and transparency in the justice system while upholding constitutional principles and human rights. Despite these objectives, several provisions, particularly Articles 1(22) and 151(2)(b), have raised concerns among legal practitioners regarding potential constitutional conflicts and ambiguities in law enforcement practices. This study aims to analyze the material review filed by advocates at the Constitutional Court, examining the constitutional aspects, legal implications, and protection of human rights within the criminal justice system. The research employed a normative legal method with a statutory and conceptual approach, using primary legal materials, relevant Constitutional Court decisions, and secondary literature. The findings indicate that the contested provisions contain vague norms that may lead to multiple interpretations, potentially enabling abuse of authority by law enforcement and reducing guarantees for a fair trial, legal aid, and due process. The study concludes that judicial review plays a critical role in clarifying legal norms, ensuring alignment with constitutional principles, enhancing legal certainty, and strengthening human rights protection. This process also underscores the strategic role of advocates in maintaining the quality of Indonesia’s criminal procedural law.